PELAKSANAAN VARIASI MENU UNTUK BREAKFAST PADA RESTAURANT HARRIS CAFE DI HARRIS RESORT WATERFRONT BATAM - Romauli Lumbangaol; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The city of Batam is the main choice when you want to visit the Riau Islands because of its strategic location across the line. HARRIS Resort Waterfront Batam is the main choice when visiting because it has attractive facilities, one of which is the Harris Cafe restaurant which is diverse with varied and creative food menus made to support guests' needs during their stay. The importance of menu variations for breakfast can also increase the satisfaction of hotel guests. The results obtained by the author in research on the implementation of breakfast menu variations in each hotel certainly have a standard menu. Basically, the menu consists of carbohydrates, protein, and fruit. According to theory, the types of breakfast menus that are often prepared by hotels are: Fruit, Cereal, Egg, Fish, Cold, Meat, Bread, Preserves, Hot Meat, and Beverages. The method used in this research is descriptive qualitative. Thus, the data obtained is based on the author's direct observation through in-depth interviews with informants. The data obtained will be processed and explained clearly using language methods that are easy to understand. There are several types of food that must be served and some are complementary foods depending on the standard of the hotel. At HARRIS Resort Waterfront Batam itself, it has done quite well during its implementation at the Harris Cafe restaurant because it rotates the menu once every 3 months, as well as forming an attractive buffet featuring various kinds of stalls, namely Egg Station, Bakery and Pastry, Butter and Jam, Cheese and Cold Out, Porridge, Pancake and Waffle Stall, Indomie Rebus Stall, Western Buffet, Slice Fruit, Salad Corner, Cereals, Crackers, Mini Stall, Indonesian Sweet, Bubur Manis Stall, Asean Buffet, Healthy Corner, Aneka Sambal, Nusantara Stall and Beverages. Keywords: Variation, Breakfast, Menu, Restaurant, Harris Café